A shoulder surfing resistance using graphical authentication system - N, Rupavathy; Mary Belinda M. J, Carmel; G, Nivedhitha (International Journal of Engineering and Technology, 2018)
AuthenticationÂ supportedÂ passwordsÂ is employedÂ mostlyÂ in applications forÂ laptopÂ security and privacy. However, human actionsÂ likeÂ selectingÂ unhealthyÂ passwordsÂ and inputting passwords in an insecureÂ approachÂ areÂ considered â€œthe weakest linkâ€Â within theÂ authentication chain.Â Instead ofÂ impulsiveÂ alphanumericalÂ strings, users tendÂ to decide onÂ passwords either short orÂ purposefulÂ for simpleÂ learning. WithÂ internetÂ applications and mobile appsÂ pilingÂ up,Â individualsÂ willÂ access these applications any time andÂ any placeÂ with Â numerous devices. This evolution bringsÂ nice convenienceÂ howeverÂ additionallyÂ will increaseÂ theÂ chanceÂ of exposing passwords to shoulderÂ surfingÂ attacks. AttackersÂ willÂ observe directly or use external recording devicesÂ to gatherÂ usersâ€™ credentials. To overcomeÂ thisÂ drawback,Â we tend toÂ planÂ a uniqueÂ authentication system Pass Matrix,Â supportedÂ graphical passwords to resist shoulderÂ surfingÂ attacks. With a one-time valid login indicator andÂ circulatoryÂ horizontal and vertical bars coveringÂ theÂ  completeÂ scope of pass-images, Pass Matrix offers no hint for attackersÂ to workÂ out orÂ slimÂ down theÂ passwordÂ even they conduct multiple camera-based attacks.Â We tend toÂ additionallyÂ enforceÂ a Pass MatrixÂ imageÂ onÂ androidÂ andÂ appliedÂ real user experimentsÂ to judgeÂ  Â its memorabilityÂ and usefulness. From the experimental result, theÂ proposed system achievesÂ higherÂ resistance shoulderÂ surfingÂ attacksÂ whereasÂ maintaining usability.